Murattal dan Mujawwad Al-Qur’an di Media Sosial Indonesia (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2018)
Al Qur’an as self referential text within a word Quran and Qul represents oral dimension involved. It is a dimension when the Quran frequently is applied as narrative object in daily life by which, according to Frédéric Deny, it is called Performative. In aesthetic receptional discourse, Al Qur’an as a text is placed as object approached beautifully. For instance, it's voiced by sound and rhythm called as murattal or Mujawwad. The oldest quranic recording is found in 1855 by S Hurgronje in which it was a starting point for the Quran to recept digitally in media matters. Around 2000, Quranic Aesthetic reception in media tools Was widespread massively, then reading Qur’an in this time using Rythm isn't a matter to be coached directly. By phenomenological approach, this research try to mapping the typology as well as the history of the reader (Qori) who change to use the social media as listener and appreciator by uploading his/her reading. The result Shows that there are three aspects influencing the reader acts in social media, 1)to show the existence of the Quran 2) religious narsism, 3)authoritative freedom.